2006
DOI: 10.1042/bj20060656
|View full text |Cite
|
Sign up to set email alerts
|

Conformational transitions induced in heparin octasaccharides by binding with antithrombin III

Abstract: The present study deals with the conformation in solution of two heparin octasaccharides containing the pentasaccharide sequence GlcN(NAc,6S)-GlcA-GlcN(NS,3,6S)-IdoA(2S)-GlcN(NS,6S) [AGA*IA; where GlcN(NAc,6S) is N-acetylated, 6-O-sulfated alpha-D-glucosamine, GlcN(NS,3,6S) is N,3,6-O-trisulfated alpha-D-glucosamine and IdoA(2S) is 2-O-sulfated IdoA (alpha-L-iduronic acid)] located at different positions in the heparin chain and focuses on establishing geometries of IdoA residues (IdoA(2S) and IdoA) both insid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 31 publications
(54 reference statements)
3
53
1
Order By: Relevance
“…1c) showed a slightly higher affinity for AT compared with the octasaccharide with AGA*IA positioned at the reducing end (Fig. 1a) (14). Nevertheless, the simultaneous presence of a small amount of AT 2 -dodecasaccharide tertiary complex cannot be excluded by STD data.…”
Section: Isolation and Characterization Of The Dodecasaccharide-mentioning
confidence: 83%
See 3 more Smart Citations
“…1c) showed a slightly higher affinity for AT compared with the octasaccharide with AGA*IA positioned at the reducing end (Fig. 1a) (14). Nevertheless, the simultaneous presence of a small amount of AT 2 -dodecasaccharide tertiary complex cannot be excluded by STD data.…”
Section: Isolation and Characterization Of The Dodecasaccharide-mentioning
confidence: 83%
“…Although an early study suggested that this domain was located prevalently toward the nonreducing end of the molecule (26), other studies suggested a more random distribution (27). In recent studies by our groups, the presence of the pentasaccharide in both sulfated and unsulfated sequences was shown, suggesting a more random distribution of the pentasaccharide along the heparin chain (14). The different order of elution on the AT affinity column of an octasaccharide mixture suggested the active role of the flanking residue in the binding of the pentasaccharide sequence with AT (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Longer AT-binding sequences, such as decasaccharides, were also previously isolated (8). The influence of the position of the pentasaccharide sequence along the oligosaccharide chains together with the knowledge of the role of the residues prolonging the active sequence toward both its reducing and nonreducing side are among the major goals of current heparin research (10). Although the active pentasaccharide AGA*IA is taken as paradigm for a unique heparin sequence targeting a specific protein (i.e.…”
mentioning
confidence: 99%